2012
DOI: 10.4012/dmj.2012-246
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic fatigue resistance of yttria-stabilized tetragonal zirconia polycrystals with hot isostatic press processing

Abstract: This study investigated the influence of surface roughness and cyclic loading on fatigue resistance in Y-TZP subjected to hot isostatic pressing (HIP). Fifty Y-TZP cylinders 3.0 mm in diameter were divided into Group A (polished by centerless method; TZP-CP) or Group B (blasted and acid-etched: TZP-SB150E). Twenty five cp-titanium cylinders (Ti-SB150E) were used as a control. Static and cyclic tests were carried out according to ISO 14801. The cyclic fatigue test was performed in distilled water at 37°C. Surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…Guilherme et al also reported that no correlation exists between surface roughness and fracture strength 33) ; however, surface treatments for ceramics often cause cracks on ceramics, which propagate internally causing mechanical strength to decrease. For yttria-stabilized tetragonal zirconia polycrystals, shot-blasted and acid-etched samples had lower fracture strengths relative to mirror polished samples 19,34) . However, crack propagation does not occur in metals because of plastic deformation caused by slip and twinning due to the existence of free electrons.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Guilherme et al also reported that no correlation exists between surface roughness and fracture strength 33) ; however, surface treatments for ceramics often cause cracks on ceramics, which propagate internally causing mechanical strength to decrease. For yttria-stabilized tetragonal zirconia polycrystals, shot-blasted and acid-etched samples had lower fracture strengths relative to mirror polished samples 19,34) . However, crack propagation does not occur in metals because of plastic deformation caused by slip and twinning due to the existence of free electrons.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, the staircase method used here can be used to quickly derive an average fatigue force with a smaller number of tests 28) . Dental zirconia implants were found to be suitable for use for long periods of time in the oral cavity after determining fracture strengths using the staircase method for various surface topographies 12,19,31) . Here, the staircase method was used to efficiently and accurately perform cyclic loading tests on a small number of samples to evaluate pure titanium durability 28) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To mimic the in vivo stress, is possible to "age" interfaces in a chewing simulator and measure the bonding effectiveness afterward (Nikaido et al, 2002;Frankenberger et al, 2003). Thereby, to simulate occlusal masticatory forces in vitro, cyclic loading is used (Koyama et al, 2012). Cyclic loading is the repeated or fluctuating application of stresses, strains or intensities to locations on structural components, and attempts to replicate the clinical conditions that zirconia restorations are subjected to due to masticatory forces (Attia and Kern, 2004).…”
Section: I533 Mechanical Degradationmentioning
confidence: 99%